Essentiality of Succinate Dehydrogenase in Mycobacterium smegmatis and Its Role in the Generation of the Membrane Potential Under Hypoxia - Ildiko Pecsi (American Society for Microbiology, 2014)
ABSTRACT Succinate:quinone oxidoreductase (Sdh) is a membrane-bound complex that couples the oxidation of succinate to fumarate in the cytoplasm to the reduction of quinone to quinol in the membrane. Mycobacterial species harbor genes for two putative sdh operons, but the individual roles of these two operons are unknown. In this communication, we show that Mycobacterium smegmatis mc2155 expresses two succinate dehydrogenases designated Sdh1 and Sdh2. Sdh1 is encoded by a five-gene operon (MSMEG_0416-MSMEG_0420), and Sdh2 is encoded by a four-gene operon (MSMEG_1672-MSMEG_1669). These two operons are differentially expressed in response to carbon limitation, hypoxia, and fumarate, as monitored by sdh promoter-lacZ fusions. While deletion of the sdh1 operon did not yield any growth phenotypes on succinate or other nonfermentable carbon sources, the sdh2 operon could be deleted only in a merodiploid background, demonstrating that Sdh2 is essential for growth. Sdh activity and succinate-dependent proton pumping were detected in cells grown aerobically, as well as under hypoxia. Fumarate reductase activity was absent under these conditions, indicating that neither Sdh1 nor Sdh2 could catalyze the reverse reaction. Sdh activity was inhibited by the Sdh inhibitor 3-nitroproprionate (3NP), and treatment with 3NP dissipated the membrane potential of wild-type or Δsdh1 mutant cells under hypoxia but not that of cells grown aerobically. These data imply that Sdh2 is the generator of the membrane potential under hypoxia, an essential role for the cell. IMPORTANCE Complex II or succinate dehydrogenase (Sdh) is a major respiratory enzyme that couples the oxidation of succinate to fumarate in the cytoplasm to the reduction of quinone to quinol in the membrane. Mycobacterial species harbor genes for two putative sdh operons, sdh1 and sdh2, but the individual roles of these two operons are unknown. In this communication, we show that sdh1 and sdh2 are differentially expressed in response to energy limitation, oxygen tension, and alternative electron acceptor availability, suggesting distinct functional cellular roles. Sdh2 was essential for growth and generation of the membrane potential in hypoxic cells. Given the essentiality of succinate dehydrogenase and oxidative phosphorylation in the growth cycle of Mycobacterium tuberculosis, the potential exists to develop new antituberculosis agents against the mycobacterial succinate dehydrogenase. This enzyme has been proposed as a potential target for the development of new chemotherapeutic agents against intracellular parasites and mitochondrion-associated disease.